Reconstructing grand theory in Islamic human geography – some preliminary notes - Amriah Buang, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2010)
To have or not to have a grand theory is the question asked and deliberated by contemporary geographers although some or many had already dismissed the legitimacy of the question altogether . This paper addresses the problem of grand theory in contemporary (Western) human geography from an Islamic perspective. It is driven by the hypothesis that the de-legitimation or the debunking of an epistemological grand theory in contemporary human geography is neither absolute, nor final, nor universal. It is essentially a Western scholarship problem presented as if it is universal. It then proceeds to demonstrate how and why an epistemological grand theory is not a problem in the Islamic approach to knowledge. Recapitulating the gist of an earlier attempt, it provides a brief account of how an Islamic epistemology would grapple with three of the main issues and challenges facing a grand theory in human geography, namely, integrating the theoretical with the empirical, unifying multi-scalar analyses, and transcending the divide between the human and the natural sciences